Determinan Perilaku Merokok Elektrik pada Remaja Berdasarkan Theory of Planned Behavior (TPB) di Kota Kupang - Regina Parley Menthari Tengko; Helga J. N. Ndun; Afrona E. L. Takaeb (Yayasan Literasi Sains Indonesia, 2025)
E-cigarettes have become a trend especially among adolescents. This study aims to examine determinants influencing e-cigarette use in adolescents based on the Theory of Planned Behavior (TPB) in Kupang City. The research was qualitative with in-depth interview. The informants were nine male teenagers using vape. Snowballing was used to select informants. The results showed that all informants had the intention to stop using vape, but they found it difficult to stop. All informants knew the dangers posed by vape but continued smoking e-cigarettes, because vape was considered safer than conventional cigarettes, could calm the mind of vapers, and was also an alternative to quitting using regular cigarettes. Peers was found to have an influence in vaping as informants tend to imitate their friends’ behavior. Perception of behavioral control facilitating the continuation of vaping was related to the ability to buy vape from informants’ income or pocket money given by parents, the perception that vape was more economical because it could be refilled, and the difficulty to stop because of addiction while inhibiting factors were parental prohibitions leading to using vape when being outside of the house. Health promotion to educate adolescents about the harmful impacts of vape was necessary. Future researchers could explore barriers and strategies in vapers to reduce the frequency of vaping.